Analyzing The Contents of Mathematics of Textbook for the tenth Grade Students In The Light Of Reading Comprehension Mathematics skills. -Analytical study- (Journal of Hama University, 2020)
This study aimed at identifying Reading Comprehension Mathematics skills, which are supposed to be available in mathematics textbook first grade secondary, and to know to what extent are these skills available in the Mathematics Textbook (2019-2020). To achieve the goals of the study used the following tools: a list of Mathematics reading Skills, a Content analysis tool. The researcher checked the validity and reliability of the used tools.Study findings: Regarding the content analysis in the light of Mathematical Communication skills, the results showed that: the skills that enhance reading Comprehension of mathematics were available in the mathematics textbooks. However, some levels were given more consideration than other levels. For example, the level analysis of applied understanding was first at the highest percentage (percentage36.66). Then, the level analysis of literal understanding had percentage (percentage31.96). The level analysis of explanatory understanding it had (percentage31.36). In addition, the results showed the differences in the levels of subordinate skills and the differences in their repetitions and ignoring some skills that did not take any opportunity to be practiced.